The Application of Organic Matter Temporarily Shifts Carrot Prokaryotic Communities in the Endosphere but Not in the Rhizosphere - Irem Bagci; Kazuki Suzuki; Rasit Asiloglu; Naoki Harada (Microorganisms, 2023)
Endophytic prokaryotes, bacteria, and archaea, are important microorganisms that benefit host plants by promoting plant growth and reducing stress. The objective of this study was to evaluate temporal shifts in the root endophytic prokaryotic communities associated with carrots (Daucus carota subsp. sativus) and the effect of organic matter application on them. Carrots were grown in a planter under five fertilizer treatments (weed compost, bark compost, cattle manure, chemical fertilizer, and no-fertilizer control) and the compositions of rhizosphere and root endosphere prokaryotic communities were determined via amplicon sequencing analysis targeting the 16S rRNA gene at 60 and 108 days after sowing. The results showed that the rhizosphere prokaryotic community compositions were stable despite different sampling times and fertilizer treatments; however, a greater temporal shift and an effect of the type of organic matter applied were observed in the endosphere prokaryotic communities. The differences in treatments resulted in significant differences in the abundance and Faith pyrogenetic diversity of the endosphere prokaryotic community. Genera, such as Burkholderia, Sphingomonas, and Rhodanobacter, that exhibit plant-growth-promoting and biocontrol activities, were detected regardless of the treatments, suggesting that they may play an important ecological role as the core endophytes in carrot roots.